Development and Effects of FTY720 Ophthalmic Solution on Corneal Allograft Survival - Liu, Zhaochuan (Sci Rep, 2015)
Fingolimod (FTY720), a novel class of sphingosine 1-phosphate receptor modulators, has received special interest among ophthalmologists, particularly given that oral administration of FTY720 has proven to effectively treat corneal graft rejection in animal models. However, no studies have examined the performance of FTY720 as an ophthalmic solution in reducing corneal rejection in high-risk corneal rejection models, and the stability and ocular irritation profile of FTY720 ophthalmic solution are also unknown. Thus, we developed 0.1%, 0.2% and 0.5% FTY720 ophthalmic solutions and evaluated their chemical stabilities under various storage conditions with high- performance liquid chromatography. To investigate the ocular irritancy of the FTY720 ophthalmic solution, New Zealand albino rabbits were subjected to the Draize test. Furthermore, classic, well-established rat allogenic penetrating keratoplasty models were used to investigate the anti-rejection efficacy of the tested FTY720 ophthalmic solutions. We found that the non-irritating 0.5% FTY720 ophthalmic solution could prolong corneal allograft survival in rats with significant efficacy for about one month. Furthermore, no significant concentration changes occurred in any of the types of FTY720 ophthalmic solutions within three months. These results revealed crucial profiles of FTY720 ophthalmic solutions and warrant further investigation and optimization of FTY720 in the anti-rejection therapy after keratoplasty.